Effects of backstep footwork patterns on ground reaction forces and leg stiffness during taekwondo roundhouse kicks - Park, H. (European Journal of Human Movement, 2025)
This study investigated biomechanical characteristics of defensive footwork patterns during Taekwondo roundhouse kicks, focusing specifically on ground reaction forces (GRF) and leg stiffness properties. Ten elite male Taekwondo practitioners executed roundhouse kicks under various footwork conditions, including angle-based variations ranging from 0° to 90° relative to the transverse axis and distance-based variations incorporating different stepping patterns. Using motion capture and force plate data, we analyzed the relationships between footwork patterns, GRF, and leg stiffness characteristics. Our findings revealed systematic relationships between backstep angle and leg biomechanics. Leg stiffness decreased significantly as backstep angle increased, ranging from 7.0 kN/m at 0° to 4.3 kN/m at 90°. Contact time and impulse showed corresponding increases with larger backstep angles. While distance variations did not significantly affect leg stiffness, they notably influenced impulse characteristics and center of mass displacement. These results provide new insights into the mechanical principles underlying effective defensive movement and counterattack execution in Taekwondo, with implications for technique optimization and training methods.